Localization of GABA-A receptor alpha-subunit mRNAs in relation to receptor subtypes - Wisden,W; Morris,BJ; Darlison,MG; Hunt,SP; Barnard,EA (Brain Res Mol Brain Res, 1989)
The distribution of 3 GABAA receptor alpha-subunit mRNAs in various regions of bovine brain has been investigated using in situ hybridization. Whereas the alpha 2- and alpha 3-transcripts are of low abundance in all regions except striatum, the alpha 1-transcript is considerably enriched in the inferior colliculus, olfactory bulb and substantia nigra, and appears to be correlated with benzodiazepine type I receptor localization.